Witchblade: rebirth (2012), volume 4 ebook - Seeley, Tim (Witchblade: Rebirth (2012), 2015)
ABSOLUTE CORRUPTION" After sealing off the main artery of an interdimensional black market trade in the supernatural, Witchblade-bearer Sara Pezzini wears a target on her back. Between Chicago's corrupt elite and common criminals, everyone wants a piece of the Witchblade-but who will get to her first? Collects WITCHBLADE #166-169 and more!. Author: Tim Seeley. Illustrator: Diego Bernard, Arif Prianto . 2013 Top Cow Productions Inc..